An ethnographic study comparing approaches to inter-professional knowledge sharing and learning in discharge planning and care transitions. Issue 6 (18th October 2019) - Waring, Justin; Bishop, Simon; Marshall, Fiona; Tyler, Natasha; Vickers, Robert
Abstract : Purpose: The purpose of this paper is to investigate how three communication interventions commonly used during discharge planning and care transitions enable inter-professional knowledge sharing and learning as a foundation for more integrated working. These interventions include information communication systems, dedicated discharge planning roles and group-based planning activities. Design/methodology/approach: A two-year ethnographic study was carried out across two regional health and care systems in the English National Health Service, focussing on the discharge of stroke and hip fracture patients. Data collection involved in-depth observations and 213 semi-structured interviews. Findings: Information systems (e.g. e-records) represent a relatively stable conduit for routine and standardised forms of syntactic information exchange that can "bridge" time–space knowledge boundaries. Specialist discharge roles (e.g. discharge coordinators) support personalised and dynamic forms of "semantic" knowledge sharing that can "broker" epistemic and cultural boundaries. Group-based activities (e.g. team meetings) provide a basis for more direct "pragmatic" knowledge translation that can support inter-professional "bonding" at the cultural and organisational level, but where inclusion factors complicate exchange. Research limitations/implications: The study offers analysis of how professional boundaries complicate discharge planning and care transition, and the potential for different communication interventions to support knowledge sharing and learning. Originality/value: The paper builds upon existing research on inter-professional collaboration and patient safety by focussing on the problems of communication and coordination in the context of discharge planning and care transitions. It suggests that care systems should look to develop multiple complementary approaches to inter-professional communication that offer opportunities for dynamic knowledge sharing and learning.